PAPR reduction in WLAN-OFDM system using code repetition technique - Ngajikin, N. H.; Fisal, N.; Yusof, S. K. (2003)
Orthogonal frequency division multiplexing (OFDM) is the best choice to achieve high data rate transmission in wireless environment. OFDM system shows many favorable property such as high spectral efficiency, robustness to channel fading and immunity to impulse interference. However, there are some obstacles in using OFDM in transmission system, which is in contrast to its advantages. One of the major drawbacks is a very high peak to average power ratio (PAPR) of the OFDM signals. Therefore this paper analyzes the capability of code repetition (CR) to reduce PAPR in WLAN/OFDM system. The analysis is on a network model designed by WLAN 802.11a standard using Matlab, a mathematical simulation software tool. The network model has been simulated in AWGN channel environment to investigate the behavior of PAPR and BER performance. The proposed technique to reduce PAPR in the WLAN/OFDM channel coding consists of two part; convolutional code and CR. Simulation model with different number of repetition has been analyzed and the results were compared with the conventional coded OFDM (COFDM). The simulation results show that the proposed technique based on CR reduces PAPR down to 5 dB compared to COFDM model.